(untitled) (Universal International Scientific Journal, 2026)
In recent decades, assessment in education has undergone a significant shift from traditional teacher-centered testing toward more learner-centered approaches that emphasize active participation, autonomy, and meaningful learning outcomes. Contemporary learner-centered assessment methods aim to capture not only learners’ final products but also their learning processes, competencies, and real-world performance. This article provides a critical overview of key learner-centered assessment approaches, including project-based assessment, performance-based assessment, portfolio-based assessment, and self- and peer-assessment. Drawing on recent theoretical and empirical studies, the paper examines the principles, pedagogical value, and practical implementation of these methods across educational contexts. Particular attention is given to their role in fostering higher-order thinking skills, learner autonomy, reflective practice, and authentic assessment of competencies. By synthesizing current perspectives, this study contributes to a deeper understanding of learner-centered assessment as a sustainable and effective alternative to traditional testing practices in modern education.